A CRITICAL REVIEW OF KAMALA MARKANDAYA'S NOVEL "A SILENCE OF DESIRE" - Shweta, Kumari (INTI International University, 2023)
In 1960, Kamala Markandaya published "A Silence of Desire," her third novel. It's an innovative step that adds new thematic complexity to her story. The author expertly dissects the marriage relationship in this insightful work. K.S.N. Rao claims that the novel succeeds on a psychological level. A Silence of Desire is a creative analysis of the mental illness of a middle-class, conservative, religious woman. The story is representative of the growing yet uneasy middle class and the conflicts and solutions that arise from inside that demographic's unique psychology and temperament. "A Silence of Desire" is a powerful and thought-provoking novel that explores the complexities of postcolonial identity, cultural collision, and the search for self-understanding. This literary masterpiece continues to captivate readers with its perceptive analysis of pressing themes that shape our interconnected society. As conventional Indian ideals and Western modernity collide, "A Silence of Desire" by Kamala Markandaya delves into the intricate complexities of culture and individual identity. Sarojini and Ravi Dandekar's marriage is challenged by their divergent views on religion, spirituality, and the evolving post-colonial Indian environment, which is at the centre of the story. This research aims to delve into the knotty problems of coming into one's own as a person in the face of competing modernist and traditionalist pressures. Sarojini's steadfast trust in the mysterious Swamy exemplifies the lasting influence of conventional wisdom and the pursuit of enlightenment. At the end of the story, the couple learns more about themselves, their culture, and the significance of maintaining a balance between tradition and modernity. (65)